Analysis of the Influence of Service Quality and Supporting Airport Facilities on Customer Satisfaction at Halim Perdanakusuma Airport - Rizko Endra Nugraha; Jermanto Setia Kurniawan; Cecep Pahrudin; Sandriana Marina; Yana Tatiana (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
Halim Perdanakusuma Airport has seen a significant rise in passenger traffic in the post-COVID-19 period, creating an urgent need to improve terminal facilities and service quality. Despite these developments, users continue to report dissatisfaction with various aspects of airport services and infrastructure. This study aims to examine the effect of terminal facilities and service quality on passenger satisfaction. Using a quantitative approach, data were collected through surveys and analyzed with multiple linear regression via SPSS. The independent variables include electronic facilities (X1), IT facilities (X2), infrastructure facilities (X3), electrical facilities (X4), and service quality (X5), while passenger satisfaction serves as the dependent variable (Y). The results show that all independent variables have a positive and significant influence on passenger satisfaction, both individually and simultaneously. Among these, electronic facilities and service quality have the most dominant impact. The F-test supports the model’s validity, confirming that the combination of variables significantly influences satisfaction levels. These findings highlight the importance of a comprehensive service strategy that integrates technology, infrastructure, and human interaction to enhance overall service quality in the aviation sector.